Utilization of Ficus benjamina by Birds at Urban Habitat in Depok - Pradana, Dimas Haryo; Mardiastuti, Ani; Yasman, Y (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2018)
Most of the research about the relationship of birds and figs were conducted at natural habitat. We conducted a research about this relationship at urban habitat in Depok and specifically studied utilization of Ficus benjamina by birds as feeding and nesting tree. The objective of our research was to describe the F. benjamina utilization by urban birds in Depok. Scans sampling and nest counting were used during this study. Our research shows that F. benjamina was used as feeding tree by most of birds which lives at urban habitat in Depok. Our research also shows that some birds used this fig species as nesting tree. Key Words : birds, Ficus benjamina, urban, Java